Knowledge, attitudes and practices with regard to the presence, transmission, impact, and control of cystic echinococcosis in Sidi Kacem Province, Morocco. Issue 1 (December 2015) - El Berbri, Ikhlass; Ducrotoy, Marie; Petavy, Anne-Françoise; Fassifihri, Ouaffa; Shaw, Alexandra; Bouslikhane, Mohammed; Boue, Franck; Welburn, Susan; Dakkak, Allal
Abstract Background This study is a component of a large research project on five major neglected zoonotic diseases (NZDs) including cystic echinococcosis and was undertaken in the Province of Sidi Kacem over a period of four years (April 2009-March 2013). Methods Questionnaires were administered at community level in a total of 27 communes and visits were made to all of the 10 abattoirs situated in the Province, to collect qualitative data on determinants of transmission for disease in humans and animals. More specifically, community knowledge, attitudes and practices related to cystic echinococcosis were assessed, as well as the extent to which local customs and behaviours may promote transmission. Abattoir infrastructure and practices, and their role in perpetuating disease transmission were also critically evaluated. Results The results show that only 50 % of people have heard of the disease, and of those, only 21 % are aware of the dog's role in disease transmission. Sixty-seven per cent of respondents stated that dogs are fed ruminant organs deemed unfit for human consumption. Owned dogs have access to the family home, including the kitchen, in 39 % of households. The extent of this close proximity between humans and animals is even more pertinent when one considers that dogs are omnipresent in the community, with an average of 1.8 dogs owned per household. The unrestricted access of dogs to abattoirs is a huge issue, which further promotes disease transmission. Conclusion This study would suggest that the high prevalence of cystic echinococcosis in humans and animals in Morocco is largely due to three factors: 1) abundance of dogs 2) engagement in risky behaviour of the local population and 3) poor abattoir infrastructure and practices. This has serious implications in terms of the socio-economic impact of the disease, especially for rural poor communities.